2016
DOI: 10.1145/2811255
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Constraint Satisfaction Requires Large LP Relaxations

Abstract: We prove super-polynomial lower bounds on the size of linear programming relaxations for approximation versions of constraint satisfaction problems. We show that for these problems, polynomial-sized linear programs are no more powerful than programs arising from a constant number of rounds of the Sherali-Adams hierarchy.In particular, any polynomial-sized linear program for Max Cut has an integrality gap of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Combining the above with the connection between Sherali-Adams gaps and extended formulations by [7,21] also yields that the basic LP is at least as strong as any LP extended formulation of size n o(log n/ log log n) . Corollary 1.2.…”
Section: Our Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Combining the above with the connection between Sherali-Adams gaps and extended formulations by [7,21] also yields that the basic LP is at least as strong as any LP extended formulation of size n o(log n/ log log n) . Corollary 1.2.…”
Section: Our Resultsmentioning
confidence: 82%
“…A connection between LP integrality gaps for the Sherali-Adams hierarchy, and lower bounds on the size of LP extended formulations, was first established by Chan et al [7] and later improved by Kothari et al [21]. In [21], the authors proved the following:…”
Section: Lower Bounds For Lp Extended Formulationsmentioning
confidence: 98%
“…This parameter characterizes semidefinite representability in much the same way that nonnegative rank captures representation as a linear program. Recently, Lee, Raghavendra, and Steurer [25] building on techniques in [11] gave the first exponential lower bounds for general semidefinite programs, but there are still many open questions in this area about both proving quantitatively stronger lower bounds and proving lower bounds for approximation versions of these representability questions. In another direction, it is not known whether there is an algorithm to decide if the semidefinite rank of a nonnegative matrix M is at most r that runs in polynomial time for r = O(1) [13].…”
Section: Question 2 Can the Nonnegative Rank Of A Matrix M Be Certifmentioning
confidence: 99%
“…Subsequently Rothvoß [Rot14] proved a 2 Ω(n) lower bound for the perfect matching polytope, which via a reduction implies the same bound for TSP. Chan et al [CLRS13] obtained lower bounds on linear extension complexity for constraint satisfaction problems via a different route: roughly put, they showed that arbitrary linear extensions are not much more powerful than the specific linear extensions produced by the "Sherali-Adams Hierarchy"; hence they could obtain lower bounds on linear extension complexity from known bounds on the Sherali-Adams hierarchy.…”
Section: Motivation: Linear and Semidefinite Extension Complexitymentioning
confidence: 99%
“…Until recently, there were only a few lower bounds for "symmetric" psd extensions [LRST14,FSP13]. However, in a very recent breakthrough, Lee et al [LRS14] generalized the approach of [CLRS13] to show that arbitrary psd extensions are not much more powerful than the specific psd extensions produced by the "Lasserre Hierarchy". In particular they showed that the TSP polytope has psd extension complexity 2 Ω(n 1/13 ) .…”
Section: Motivation: Linear and Semidefinite Extension Complexitymentioning
confidence: 99%